Does depression matter in neuropsychological performances in anorexia nervosa? A descriptive review. Issue 6 (29th May 2015) - Abbate‐Daga, Giovanni; Buzzichelli, Sara; Marzola, Enrica; Aloi, Matteo; Amianto, Federico; Fassino, Secondo
ABSTRACT Objective This review aims to examine the impact of depressive symptoms on the assessment of cognitive flexibility, central coherence, and decision‐making in individuals with anorexia nervosa (AN). Method An online search was carried out using PubMed and PsycInfo. Articles were selected for review if they were published in English between 1990 and 2014 and used the Wisconsin Card Sorting Test, the Trail Making Task parts A and B, the Brixton Test, the Rey‐Osterrieth Complex Figure Test, and/or the Iowa Gambling Task. Results Sixty‐two studies were included. Thirty (48%) of the studies statistically assessed the association between depression and neurocognition in AN versus healthy controls. Where significant correlations were found, it became clear that the more serious the depression, the greater the neuropsychological impairment. Only six (10%) studies examined whether increased depressive symptoms were able to eliminate the differences between individuals with AN and healthy controls, and one study found that depressive symptoms did eliminate group differences in cognitive flexibility and decision‐making. Discussion Only a subgroup of articles on neuropsychology in AN adjusted for depression. However, given the role of depression that some articles suggest, future studies should pay closer attention to the evaluation of this potential confounder. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:736–745)